2022
DOI: 10.3390/ijerph192113723
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Perceived Likelihood of Receiving COVID-19 Vaccine

Abstract: There are limited studies on the perceived likelihood of receiving a COVID-19 vaccine among the general US population and its subpopulations. We examined the association between the perceived likelihood of receiving a COVID-19 vaccine with the self-reported likelihood of contracting COVID-19, social-distancing stress, COVID-19 diagnosis status, mental health disorders, and sociodemographic characteristics. The data were collected using a national cross-sectional survey (N = 5404) between 13 May 2021 and 9 Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
(61 reference statements)
1
3
0
Order By: Relevance
“…Additional studies should be initiated to explore strategies that may increase COVID-19 vaccination rates among younger age groups. Furthermore, our results showed that more than a third of respondents with either a high school degree or some college were not vaccinated, which is consistent with existing research that individuals with lower educational levels showed higher hesitancy towards COVID-19 vaccination and reported lower vaccination rates [22,32]. Individuals with lower education levels may have limited science health literacy, influencing confidence in the safety and effectiveness of the vaccine.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additional studies should be initiated to explore strategies that may increase COVID-19 vaccination rates among younger age groups. Furthermore, our results showed that more than a third of respondents with either a high school degree or some college were not vaccinated, which is consistent with existing research that individuals with lower educational levels showed higher hesitancy towards COVID-19 vaccination and reported lower vaccination rates [22,32]. Individuals with lower education levels may have limited science health literacy, influencing confidence in the safety and effectiveness of the vaccine.…”
Section: Discussionsupporting
confidence: 90%
“…Prior to availability of the COVID-19 vaccine, studies showed that Asians and Hispanics/Latinos reported greater intentions to get the vaccine and Black non-Hispanic/non-Latinx were more hesitant to get the vaccine if a vaccine was approved [20,21]. This pattern is still evident as studies conducted during the post-vaccine period show that Black non-Hispanics were less willing to get the COVID-19 vaccine compared to other racial and ethnic groups [22,23]. There are also known trends in racial and ethnic differences regarding general adult vaccinations, with minority populations having lower vaccination rates [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that individual-level factors may have affected the association between these county-level vaccination barriers and willingness to receive the COVID-19 vaccine by serving as confounders and/or mediators in these relationships. The influence of the individual-level sociodemographic covariates on willingness to receive the COVID-19 vaccine is consistent with previous literature (22,(34)(35)(36) and further suggests that many sociodemographic characteristics associated with COVID-19 vaccination intentions vary systematically across counties in the U.S.…”
Section: Figuresupporting
confidence: 88%
“…Interestingly, we also found sexual minority individuals with mild anxiety/depression symptoms had the highest likelihood of receiving the COVID-19 vaccine, but individuals with moderate and severe anxiety/depression had a lower likelihood of vaccination. Prior research in this area is inconsistent, with some showing individuals with mental health conditions are more likely to be vaccinated [ 44 , 45 ], others showing they are less likely [ 43 , 46 , 47 , 48 ], and some showing variability in vaccination by the type and severity of mental health symptoms [ 44 ]. We provide evidence of heterogeneity in vaccine intent by sexual orientation and level of anxiety/depression symptoms, illustrating individuals with mild and severe anxiety/depression may be the most at risk for being unvaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…Avoidance of medical care because of perceived discrimination has been documented among racial/ethnic and sexual minority groups [ 63 , 64 , 65 ]. Thus, discrimination experiences may also lead to vaccine hesitancy [ 48 ], highlighting a need to improve trust and engagement in healthcare settings with populations vulnerable to discrimination. Interestingly, sexual minority individuals who experienced discrimination once a month had the highest perceived probability of receiving the COVID-19 vaccine, indicating a deviation from prior literature [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%